Comment jouer aux codes littéraires ? (À l’exemple des contes insolites français du XXe siècle) - Komandera, Aleksandra (Romanica Silesiana)
One of the essential features of the twentieth century French uncanny tales is a play with literary conventions. According to the postmodern aesthetics, these short fictions give priority to all kinds of transgressions on the level of both the content and the form. The aim of the study is to describe the play with the literary codes on the basis of short fictions of G. Apollinaire, M. Aymé, B. Vian, P. Gripari, J. Supervielle, M. Tournier, Ph. Dumas and B. Moissard, P. Fleutiaux. The authors invite the readers to take part in the ludic activity and let the perception of the uncanny tales depend on their familiarity with the related categories of the marvellous and the fantastic, and on their knowledge of intertextuality rules. Key words: Short fiction, the uncanny, the fantastic, the marvellous, literary conventions, cultural code.